Komunikasi Efektif terhadap Pendidikan SDN 040522 Desa Tambunan, Rumamis, Kecamatan Barusjahe, Kabupaten Karo - Nurhikmah Fadilah; Najiah Maisaro Br Nst; M. Fachri Anwar; Samir Humaidi; Zahra Saritza (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2022)
In communicating between teachers and students must use the right Indonesian language, so that effective communication can be realized. This type of research uses qualitative research methods. Data collection techniques were obtained from interviews, observations and documentation. The data analysis method used in this study used a descriptive analytical approach. Based on the output of the research, it was found that teachers experienced obstacles in managing the class, especially in attracting students' attention, giving instructions, revealing dan applying class rules dan mechanisms as a result, effective communication in class management has not been achieved, while in delivering subject, effective communication is relatively built. Because students are actively involved. Delivering the right information is very important for teachers to do, especially in creating effective communication because it really determines the success or failure of learning activities by taking into account the developmental characteristics of students. Christian teachers also act as facilitators who reflect Christian values in every pedagogy they do.